Вибір показників теплової надійності огороджувальних конструкцій - Пашинський, В. А.; Джирма, С. О.; Плотніков, О. А.; Pashynskyi, V.; Dzhyrma, S.; Plotnikov, O. (Луцький НТУ, 2017)
На базі аналізу рівня теплової надійності огороджувальних конструкцій, запроектованих згідно з вимогами ДБН В.2.6-31:2016, розроблені отримано допустимі значення відносної тривалості теплових відмов за критеріями комфортності перебування поблизу стін та утворення конденсату на їх внутрішній поверхні. The article discloses suggestions for the selection of an appropriate level of thermal sufficiency of the walling of residential and public buildings. As an indicator of thermal sufficiency it is recommended to use the relative duration of the state of thermal failure. According to the method developed earlier the relative duration of the thermal failure condition of walling has been determined. The resistance to heat transfer in the conditions of different regions of Ukraine corresponds to the requirements of the current thermal insulation of buildings on the absence of condensation on the internal surfaces of walls and the comfort of staying at external walls. The obtained results vary significantly across the territory but their generalization to the safety margin allowed establishing the maximum permissible value of the relative duration of the thermal failure state equal to 0.005 for the walls of residential and public buildings of the sufficiency class CC 2 and 0.001 for the buildings of the sufficiency class CC 3.
The choice of indicators of thermal reliability of walling
Keywords: огороджувальні конструкції; теплова надійність; теплова відмова; критерій комфортності; критерій утворення конденсату; walling; thermal sufficiency; comfort criterion; thermal failure; criterion of condensate formation